Benign hepatic tumors in childhood: surgical resection and outcomes - Alaa Younes; Ahmed Elgendy; Sayed Fadel; Habiba Elfandy; Marwa Romeih; Madeeha Elwakeel; Gehad Ahmed (SpringerOpen, 2023)
Abstract Background Primary hepatic neoplasms in pediatric age are rare entities. Clinical and survival data in children with benign liver tumors who were treated by surgery are still negligible. We aimed to present a tertiary oncological center experience regarding surgical management and outcomes of pediatric benign hepatic tumors. Material and methods A retrospective chart review was performed including all children with benign liver tumors who were surgically managed at our institution from January 2014 to January 2022. Patients' demographics, presentations, imaging scans, pathological subtypes, operative details, complications that happened, and overall outcomes were discussed. Results One-hundred ninety-three children with liver tumors were referred to our center, and 28 of them had benign tumors (14.5%). Ten patients were managed by medical therapy (all were IHH/hemangiomas), and the remaining 18 were treated by surgery. Of the 18 patients; there were 10 females (55.5%), and the median age at diagnosis was 24 months (range: 5-108 months). Palpable abdominal mass was the main symptom in 14 patients (77.8%). Eleven patients (61%) were PRETEXT II, while the remaining 7 (39%) were PRETEXT I. The median tumor size was 10.9 cm (range: 7.2-18 cm). Preoperative biopsy was conducted in 12 patients (66.7%). Seventeen patients had primary resection, while the remaining child with IHH/hemangioma underwent delayed surgery. Twelve cases had segmental resection or sectionectomy, and hemihepatectomy was performed in the remaining six. The resection rate of benign tumors versus all liver resections at our center during the study period was 12% (18/151). There were no intraoperative complications encountered in any patient. Only one patient developed biliary leakage on the 5th postoperative day which was managed conservatively. At a median follow-up time of 40 months, there were no deaths or recurrences among the included patients. Conclusions Surgical resection is the principal modality of management for the majority of pediatric benign liver tumors, which constituted 12% of our hepatic resection rate. Complete excision with negative margins can be performed without significant morbidity for such tumors, and it achieves excellent clinical and long-term oncological outcomes.